Underperforming light curing procedures trigger detrimental irradiance-dependent biofilm response on incrementally placed dental composites. (September 2019) - Maktabi, Haifa; Ibrahim, Maria; Alkhubaizi, Qoot; Weir, Michael; Xu, Hockin; Strassler, Howard; Fugolin, Ana Paula P.; Pfeifer, Carmem S.; Melo, Mary Anne S.
Abstract: Objectives: Insufficient radiant exposure (J/cm 2 ) may provide an early trigger in a cascade of detrimental responses on incrementally-place composite, especially the bottom layer. This study aimed to assess the influence of poor radiant exposure, the degree of conversion (%DC), water sorption/ solubility and S. mutans biofilm formation on conventional, incrementally placed composites and to establish a relationship between these factors. Methods: Two light units operating at 600 and 1000 mW/cm 2 and four most common operator-dependent curing conditions had the radiant exposure (RE ) recorded. All the specimens were subjected to S. mutans biofilm model for 14 days. The %DC, biofilm formation expressed by colony-forming units (CFU), water sorption/ solubility and surface roughness/ SEM were assessed. Data were submitted to two-way ANOVA and Tukey post-hoc test (α = 0.05). Pearson correlation was also determined. Results: The influence of RE on S. mutans CFU values and DC are dependent on the curing conditions and irradiance (p < 0.05). A negative relationship was observed between RE and biofilm formation. The operator-dependent curing conditions have shown RE reduction varying from 49.4% to 73.5% in relation to control. The difference in DC between top/bottom of cylinder varied from 13% to 21% for 1000 mW/cm 2 and from 29% to 53% for LCU600. The roughness, solubility and salivary sorption were greater for low RE . Conclusion: Poor, deficient curing procedures provide an early trigger in a negative pathway of events for incrementally-place dental composite including a biological response by increased biofilm formation by S. mutans, a relevant factor for secondary caries development. Significance: The susceptibility to variation in the outcomes was RE -dependent. The optimization of the curing procedures ensures the maximum performance in the chain of events involved in the light curing process of resin-based materials and potentially reduce the risk factors of secondary caries development.